LINGUODIDACTIC FOUNDATIONS OF USING DIGITAL TECHNOLOGIES IN THE FORMATION OF WRITTEN SPEECH SKILLS IN ENGLISH - Tojibayeva, N. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
This article can inform the lingvodidactic features and the place of digital technologies of improving writing skills of pupils at the education schools. The digital technologies are progressing and pupils widely use digital technologies on learning languages. They improve their writing skill by the help of digital technology. While you are reading this article, you will have information about the lingvodidactics and important aspects of writing skills and their description. The author of the article presents the linguistic and didactic functions of written speech and their descriptions.
Keywords: digital technologies; lingvodidactics; writing; skill; style